"Challenging Professional Boundaries": A Grounded Theory Study of Health Professionals' First Experiences of End-of-Life Care in Hospital. (August 2022) - Finotto, Stefano; Artioli, Giovanna; Bodecchi, Simona; Mainini, Carlotta; Pedroni, Cristina; Di Leo, Silvia; Ghirotto, Luca; Hayter, Mark; Tanzi, Silvia
Little is known about health professionals first experiences of End-of-Life care in hospital. This study aims to understand the psycho-social process that occurs when hospital-based health professionals engage in caring for a dying patient for the first time. We conducted a Grounded Theory study, with 19 health professionals. Challenging professional boundaries is the core category which explains the overall process. The theoretical model we conceptualized evidenced three phases: 1) building a relationship between patient/family and professionals, 2) the disrupting impact and 3) the reaction phase. Our analysis highlighted the initial strong impact of this experience, which brought professionals to perceive emotional suffering and feelings of inadequacy. The new aspect our grounded theory revealed is that all the categories are pertinent to all the professionals involved, therefore they explain important aspects of interprofessional collaboration in End-of-Life care.